Gender differences in performance in competitive environments: evidence from professional tennis players - Marco Daniele Paserman (Institute for the Study of Labor (IZA), 2007)
This paper uses data from nine tennis Grand Slam tournaments played between 2005 and 2007 to assess whether men and women respond differently to competitive pressure in a setting with large monetary rewards. In particular, it asks whether the quality of the game deteriorates as the stakes become higher. The paper conducts two parallel analyses, one based on aggregate set-level data, and one based on detailed point-by-point data, which is available for a selected subsample of matches in four of the nine tournaments under examination. The set-level analysis indicates that both men and women perform less well in the final and decisive set of the match. This result is robust to controls for the length of the match and to the inclusion of match and player-specific fixed effects. The drop in performance of women in the decisive set is slightly larger than that of men, but the difference is not statistically significant at conventional levels. On the other hand, the detailed point-by-point analysis reveals that, relative to men, women are substantially more likely to make unforced errors at crucial junctures of the match. Data on serve speed, on first serve percentages and on rally length suggest that women play a more conservative and less aggressive strategy as points become more important. I present a simple game-theoretic model that shows that a less aggressive strategy may be a player's best response to an increase in the intrinsic probability of making unforced errors.
urn:nbn:de:101:1-2008032804
Keywords: 330; Geschlecht; Stress; Verhalten; Professioneller Sport; Spieltheorie